PROCJENA FLEKSIBILNOSTI ZADNJE LOŽE BUTA KORIŠĆENJEM DVA RAZLIČITA MJERNA INSTRUMENTA - Bakirtzoglou Panteleimon; Ioannou Panagiotis; Bakirtzoglou Fotis (University of Banja Luka, Faculty of physical education and sport, 2010)
The purpose of the present study was to investigate the effect of two different methods ofmeasurement for hamstring flexibility. Forty male students athletes with mean age 23.45±0.44years and forty non-athletes students with a mean age 23.08±0.98 years participated in this study.Hamstring flexibility was evaluated by two different methods of measurement: a) a Myrin goni-ometer and b) sit and reach test. Statistical analysis included the use of Independent Samples T-test while significance was set at p<0.01. The results indicated that athletes students scored betterthan non-athletes students only when hip joint's mobility was measured with a Myrin goniometer.In conclusion the evaluation of joint's mobility should be done by using a method of measure-ment that would isolate the articulation of measurement from the interjection of other joints ormuscular teams something that is achieved by the use of Myrin goniometer than the use of Sitand Reach test.